Interactions between 2 subtypes of central sensitization in rats and humans: spinal long-term potentiation and brainstem controls : commentaries - Treede, Rolf-Detlef (Pain, 2024)
An abstract is unavailable.
Online verfügbar: 2. Januar 2024
Gesehen am 23.10.2024